Behavioural intention to use artificial intelligence (AI) among accounting students: evaluating the effect of technology readiness / Jyashree Krishnanraw and Kamisah Ismail - Krishnanraw, Jyashree; Ismail, Kamisah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This research examined the factors influencing Malaysian accounting students’ use of Artificial Intelligence (AI) through an extended Technology Acceptance Model. Amid the growing integration of AI in Asia’s accounting sector, this study examined the perceptions and intentions of future professionals toward its use. A cross-sectional, survey-based methodology was employed, targeting third and fourth-year undergraduate students from four prominent Malaysian universities, both public and private. The survey evaluated technology readiness aspects, including optimism, innovativeness, discomfort, and insecurity, alongside superior functionality and perceived usefulness. Data from 136 respondents were analysed using Smart PLS 4, assessing the direct and indirect influences on the behavioural intention to use AI. The results revealed that optimism and innovativeness positively impacted perceptions of AI’s functionality, with optimism additionally affecting perceived usefulness. However, these factors did not significantly enhance the intention to use AI. Notably, superior functionality acted as a crucial intermediary, linking positive perceptions with usage intentions. In contrast, discomfort adversely affected this intention, highlighting it as a significant barrier to AI engagement. The f indings highlight the need for curricular updates in accounting education to mitigate technological discomfort and emphasize critical areas for enhanced AI integration and engagement, aligning with technological progress and the profession’s changing demands.